Research on the impact of the blockchain-authenticated information on consumers' perception towards traceable products: Evidence from JD - Luona Song; Jiayin Qi; Tingjie Lu; Kai Zhang (International Telecommunications Society (ITS), 2019)
This paper examines the moderating effect of the blockchain-authenticated information to an individual's perceived level of uncertainty and thus influences personal affection and cognition processes in online shopping behaviors. The perceived level of uncertainty hides in consumers' emotions of online reviews and is captured through the code of TextMind (a simplified Chinese version of LIWC). The study reveals several interesting insights about blockchain-equipped products. First, the blockchain-authenticated information is perceived by final consumers to some extent and thus decreases the level of uncertainty compared with non-blockchain-involved products in the same category. Secondly, the increase of perceived uncertainty is confirmed by the percentage of two negative emotions each relates a different level of uncertainty (anxiety often refers to a higher level of uncertainty while anger is usually expressed when uncertainty is low). Thirdly, the results also show the double-edged effects of blockchain-authenticated information (e.g. traceability assurance of the product) as it may enrage consumers and thus decrease their brand loyalty if the guaranteed quality is not fit with that of actual products. The study provides vivid evidence of blockchain attempts in improving the current supply chain and offering extra values to related parties.
Keywords: 330; Online reviews; traceable products; blockchain technology; emotions; anxiety; anger